Development of a fluvoxamine detection system using a Quenchbody, a novel fluorescent biosensor. Issue 4 (26th November 2018) - Sasao, Ako; Takaki, Michiyo; Jeong, Hee‐Jin; Yonemitsu, Kosei; Ohtsu, Yuki; Tsutsumi, Hiroshi; Furukawa, Shota; Morioka, Hiroshi; Ueda, Hiroshi; Nishitani, Yoko
Abstract: The misuse of psychotropic drugs intended for medical treatment represents a recent worldwide public health concern. Quenchbody (Q‐body) is a novel fluoroimmunosensor that can detect an antigen immediately without additional reagents or washing steps. Here, we describe creating Q‐bodies for the detection of the antidepressant fluvoxamine (FLV) and determining optimal conditions to achieve the highest fluorescence intensity (FI). We prepared five Q‐bodies with the fluorophore labeled at either the N‐ or C‐ terminus and with different linker lengths. Fluorescence was measurable within minutes, indicating the interaction of Q‐bodies with FLV. The normalized FI (FI ratio) of the N‐terminus labeled Q‐body increased approximately 1.5‐fold upon FLV addition; Q‐bodies labeled at the C‐terminus did not significantly increase FI. Among the fluorescence dyes used in this study, Rhodamine 6G labeled Q‐body showed the best FI ratio. EC50 values of the N‐terminus labeled Q‐bodies were similar (23.2–224nM) regardless of linker length or labeling dye. We examined whether the Q‐body could be applicable to serum matrix instead of phosphate‐buffered saline. The intact serum interfered strongly with the Q‐body fluorescence. However, the FI ratios of the Q‐body for FLV‐spiked serum filtrate, for which proteins were removed by filtration, showed a dose‐dependency for detecting FLV levels. Deproteinization, which does not interfere with Q‐body fluorescence measurements, is likely necessary to detect serum FLV with high sensitivity. This study demonstrates the potential of Q‐body probes as a tool towards developing creative immunoassay applications. Abstract : We describe creating fluoroimmunosensor Quenchbody (Q‐body) for the detection of the antidepressant fluvoxamine (FLV) and determining optimal conditions to achieve the highest fluorescence intensity. The Q‐body whose fluorophore was labeled at the N‐terminus with the shorter linker length showed the best fluorescence intensity and Rhodamine 6G was suitable for the labeling fluorescence dye. Our results showed that the Q‐body could detect therapeutic serum level of FLV within minutes.